Health Impact of Indoor Air Pollution - Joshi, HD; Pandeya, R; Dhakal, B (Journal of Nepal Health Research Council, 2010)
Background: The domestic smoke exposure increases the risk of a range of common and serious diseases. Further, association of exposure with chronic bronchitis and chronic obstructive lung disease is quite well established in recent researches. This work was carried out to determine the health impact of indoor air pollution in rural hill region of Nepal. Methods: A cross-sectional study on health impact of indoor air pollution to exposed kitchen dwellers and children, was done using random sampling method devised with probability proportion in Malikarjun Village Development Committee, Nepal. This study was conducted in two phases, in first phase. Adult kitchen dwellers were assessed for prevalence of respiratory disorder while in second phase, during three months Acute Respiratory Infection episodes of children below two years were recorded. Results: Eight kinds of respiratory ailments and related symptoms were prevalent in adult respondents of 42 households. Cough phlegm, breathlessness, wheezing, chronic obstructive pulmonary disease, and bronchial asthma were significantly varied with higher exposure category (P<0.05) and smoking habit (P<0.01). Peak expiratory flow rate PEFR results significantly varied with both smoking habit and exposure level both in male and female (P<0.01). Correlation analysis denoted higher prevalence of diseases and symptoms in smokers (r = 0.464; P<0.01). Acute Respiratory Infection episodes per child was significant in grade I (P<0.01) and grade II (P<0.05) for both exposure level and parental smoking habit. Conclusions: A significant association between exposure of Indoor Air Pollution and prevalence of respiratory disorders and related symptoms in kitchen dwelling adults and children was found. Key words: acute respiratory infection; exposure duration; indoor air pollution; prevalence; respiratory disorder. DOI: 10.3126/jnhrc.v7i2.3009 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 69-75